Carbonylation of glycerol with urea to glycerol carbonate over supported Zn catalysts - Kondawar, S. E.; Mane, R. B.; Vasishta, A.; More, S. B.; Dhengale, S. D.; Rode, C. V. (Applied Petrochemical Research, 2017)
Glycerol carbonylation with urea is a very feasible option to produce glycerol carbonate with a net result of CO2 fixation through urea synthesis. The prerequisite of an efficient catalyst for this reaction is to possess both acid and basic sites together. Several acidic supports were screened for ZnO catalyst in this work and Zn/MCM-41 was found to exhibit the best activity and almost complete selectivity to glycerol carbonate (GC). Although, non-catalytic glycerol carbonylation resulted in GC formation but glycerol conversion achieved was twice with Zn/MCM-41 as a catalyst. Further to that increase in Zn loading from 2 to 5% resulted in increase in glycerol conversion from 63 to 82%. The prepared catalysts were characterized by XRD, NH3 and CO2-TPD and effects of reaction parameters such as catalyst loading, glycerol to urea mole ratio and temperature on glycerol conversion and GC selectivity in batch mode of operation were also studied. Time on stream activity of 5% Zn/MCM-41 catalyst for continuous carbonylation of glycerol was also studied for ~100 h with an average conversion of ~55% and complete selectivity to GC. This indicated five times lower productivity of GC per h due to lower residence time than that in a batch operation as compared to that of a continuous operation. Activation energy estimated from the Arrhenius plot was found to be 39.82 kJ mol−1 suggesting that the reaction is kinetically controlled. A reaction pathway mediated by acid and basic sites of the Zn/MCM-41 catalyst is also proposed.
Keywords: Acid–base ratio; Continuous process; Glycerol carbonate; Glycerol-urea carbonylation; reaction pathway; Supported Zn; Zn loading